PENGARUH KEMUDAHAN PENGGUNAAN, MANFAAT DAN RISIKO TERHADAP MINAT NASABAH MENGGUNAKAN MOBILE BANKING BANK SYARIAH - Muhammad Qoes Atieq; Eva Nurpiani (LP2M Universitas Bina Bangsa, 2022)
IAIN Sharia Banking Student Sheikh Nurjati Cirebon as a student who learns about Islamic banking and has sufficient knowledge about mobile banking. Therefore, it is necessary to research whether there is an interest in students who are BSI customers to use mobile banking with independent variables that are used for ease of use, benefits and risks. The method used is a quantitative method with data collection techniques through questionnaires. The population in this study was IAIN Sharia Banking students Sheikh Nurjati Cirebon with a total sample of 91 people. The data analysis techniques used in this study are descriptive analysis and statistical analysis in the form of validity tests, reliability tests, classical assumption tests, multiple linear regression tests, coefficient of determination tests (R2), hypothesis tests in the form of t tests (partial) and F tests (simultaneously) using SPSS Statistics Version 23. The results of this study show that ease of use does not have a positive and significant influence on the interest in using mobile banking. The benefits have a positive and significant effect on the interest in using mobile banking. Meanwhile, risk does not have a negative and significant influence on the interest in using mobile banking. Simultaneously, ease of use, benefits and risks have a positive and significant effect on the interest in using mobile banking